Analysis of nanofluid flow and heat transfer behavior of Li-ion battery modules. (July 2023) - Sirikasemsuk, S.; Naphon, N.; Eiamsa-ard, S.; Naphon, P.
Highlights: The predicted results agree with the experimental results an average error of 1.28%. Coolant-improved flow direction and thermophysical properties significantly affect the decreasing maximum operating temperature and temperature gradient across a cell. The highest temperatures of the battery module are 30.06 °C, 30.00 °C, 29.91 °C, 29.89 °C, and 29.49 °C for models II, IV, III, I, and V. The maximum temperature gradient across a cell, models I, II, and III give the highest value [0.42 °C], and consequently, models [0.40 °C] and model v [0.15 °C]. Abstract: The operating battery temperature significantly affects electric vehicle performance, reliability, and safety. Therefore, batteries need to keep within the operating temperature design. The 3D Eulerian model is applied to determine battery thermal behavior with five different flow directions of coolant throughout the battery pack jacket. The computational domain consists of sixty cylindrical Li-ion cells inserted into the cooling module socket with constant power input conditions. The predicted results are consistent with the experimental results, with an average error of 1.28%. Coolant-improved flow direction and thermophysical properties significantly affect the decreasing maximum operating temperature and temperature gradient across a cell. The highest temperatures of the battery module are 30.06 °C, 30.00 °C, 29.91 °C, 29.89 °C, and 29.49 °C for models II, IV, III, I, and V, respectively. In addition, for the maximum temperature gradient across a cell, models I, II, and III yield the highest value [0.42 °C], followed by models IV [0.40 °C] and model V [0.15 °C], respectively. The proposed battery nanofluid cooling pack can therefore optimize the thermal management system of the EV pack.